Young Lives school survey in Peru: design and initial findings - Guerrero, G; Leon, J; Rosales, E; Zapata, M; Freire, S; Saldarriaga, V; Cueto, S (Young Lives, 2012)
This paper presents the methodology and initial findings from the Young Lives School Survey in Peru, which looked at inequality in educational opportunities and outcomes of children from the Young Lives study. Information was collected in 132 schools in nine regions of Peru, covering school quality (inputs available at school such as its infrastructure, and educational processes within classrooms such as the social and pedagogical interactions that constitute the classroom climate), responsiveness to students’ needs and potential (e.g. instruction in their mother tongue, support for students at risk of dropping out), as well as achievement and socio-emotional outcomes. A wide range of instruments was used to collect the data, including questionnaires which were completed by students, teachers, and head teachers; sociolinguistic questionnaires for children living in bilingual areas; achievement tests in maths and reading comprehension; teacher attendance; and an assessment of mathematics teachers’ pedagogical content knowledge. The survey also included a qualitative sub-study of how indigenous students experience schooling in different educational contexts. Data were collected from a sub-sample of students, teachers, and caregivers through interviews, focus groups, and school observations. Overall, preliminary results show that there are important differences in the background of students attending different types of school, which suggests that the Peruvian educational system may be reinforcing social inequalities. The qualitative sub-study showed similar results, with indigenous children’s schooling experience often not aligned with their linguistic and cultural backgrounds.